2020
DOI: 10.3390/ijerph17165925
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Participation in Physical Activity Among Canadian School-Aged Children with Autism Spectrum Disorder: An Application of the International Classification of Functioning, Disability and Health

Abstract: We have a limited understanding of the socioenvironmental factors associated with participation in physical activity among school-aged children with autism spectrum disorder (ASD), particularly regarding how the school environment may influence their participation. Using the International Classification of Functioning, Disability and Health (ICF) as a framework, this study examined the effect of body functions and structure, activity, and personal factors on in-school physical activity; and whether in-school p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Play is an essential element in the development of children’s motor skills and is intrinsically linked to enjoyment, which serves as a motivation for children to engage in physical exercise [ 46 ]. According to Bremer et al, a study demonstrated that children between the ages of 6 and 13 with autism who enjoyed their physical education sessions were more likely to engage in other physical activities [ 47 ]. Academic competition at school is an important factor that hinders the development of enjoyable feelings in teens, this is mostly caused by the negative effects of stress-induced depression and anxiety [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Play is an essential element in the development of children’s motor skills and is intrinsically linked to enjoyment, which serves as a motivation for children to engage in physical exercise [ 46 ]. According to Bremer et al, a study demonstrated that children between the ages of 6 and 13 with autism who enjoyed their physical education sessions were more likely to engage in other physical activities [ 47 ]. Academic competition at school is an important factor that hinders the development of enjoyable feelings in teens, this is mostly caused by the negative effects of stress-induced depression and anxiety [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, based on this, it is analyzed and affirmed that physical activity improves the health and quality of life of the population evaluated. The quality of the comprehensive school programs of physical education and / or physical activity can play a much more significant role for those students who present ASD, since the environment that exists in the school context can offer the opportunity to promote the development of skills and / or essential skills for students to be more active and energetic and, at the same time, to be able to make a transcendent contribution to the general levels of physical exercise in the school population (Bremer et al, 2020).…”
Section: Findings Of the Review And Contrast With The Existing Evidencementioning
confidence: 99%
“…In this sense, physical activity programs (i.e. any programs that includes any body movement produced by skeletal muscles that involves expenditure of energy (WHO, 2018)) at school have been suggested as a particularly useful means to develop and increase interest and participation in physical activity in this population (Bremer et al, 2020), allowing the introduction of behavior modification techniques through this type of programs (Fessia et al, 2018). However, the characteristics of physical activity programs that contribute to the comprehensive health of children and young adults with ASD in educational contexts are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, behavioral problems or preferences among this population (e.g., restricted interests, inflexible schedules, and preference for predictable, structured activities) may limit their PA choices (e.g., playing games, transportation, and engaging in chores, recreation, and other unstructured activities) [ 24 , 25 ]. Numerous studies have demonstrated that children and adolescents with ASD across countries (e.g., United States and Canada) do not meet the international PA recommendations [ 26 , 27 , 28 , 29 ]. For example, McCoy and Morgan examined the PA levels of 1036 American children and adolescents with ASD aged 10–17 and found that only 11% of adolescents with ASD met the international PA guidelines [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, McCoy and Morgan examined the PA levels of 1036 American children and adolescents with ASD aged 10–17 and found that only 11% of adolescents with ASD met the international PA guidelines [ 28 ]. The results of Bremer et al also showed that only 14.9% of Canadian children and adolescents with ASD aged 6–13 years met the international PA guidelines in their study [ 27 ]. Previous studies also proved that the PA levels of children and adolescents with ASD were lower than those of their peers without disabilities [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%